Answer:
(9, -1)
Step-by-step explanation:
Y=(-x*x)-4x+3
y=-(x^2+4x-3)
4+y=-(x^2+4x+4)+3
y+4=-(x-2)^2.) +3
-4. -4
y=-((x-2)^2)-1
Answers:
Vertex: (2,-1)
AOS:x = 2
Domain: All Real Numbers
Range:[-1,Infinity)
Answer: 4
Step-by-step explanation:
i think
Answer:
24 feet in lenght and 15 in width
Step-by-step explanation:
We know the total tickets sold = 400.
Let x be the number of adult tickets sold.
That means 400 - x is the number of student tickets.
The revenue from adult tickets will be $3 * x, which we can call 3x.
The revenue from student ticks will be $2 * (400 - x), or 800 - 2x.
The total revenue is $1050, so that means:
3x + (800 - 2x) = 1050.
Removing the parentheses:
3x + 800 - 2x = 1050
Subtracting 800 from both sides:
3x - 2x = 250
Simplifying the left side:
x = 250, which is the number of adult tickets.
400-x = student tickets = 400-250 = 150.
ALWAYS check!
In this case, check the revenue:
3x = 3(250) = 750
2(150) = 300
750 + 300 = 1050. Check!